Unleashing Central America’s Growth Potential : El Salvador - Ulku, Hulya (World Bank, Washington, DC, 2021)
Although El Salvador’s modest pace of growth has reduced poverty and inequality in recent years, it has not been sufficient to move the country toward the income levels of wealthier economies. The objective of this study is to investigate the drivers and constraints of growth and productivity in El Salvador from 1990 to 2017 and explore areas with high growth potential. The value added of this study is to provide an in-depth analysis of the drivers and constraints of El Salvador’s growth using a wide range of analytical tools. Historically, El Salvador’s growth is driven by factor accumulation, both labor and capital, and not overall productivity. The binding constraints for growth are identified as: (i) security, (ii) innovation, (iii) human capital, (iv) property rights, (v) limited access to finance for small firms, and (vi) corruption. Higher productivity and output growth can be achieved through quality upgrading and an export diversification strategy focused on metal, plastic, and chemical products. The country’s strategic location with access to many markets, a growing labor force, and a solid industrial base can support the expansion of the tradable sector to achieve higher and more inclusive growth. Development goals can be achieved with a long-term commitment to structural reform and investment.